2017
DOI: 10.1007/s10661-017-5943-1
|View full text |Cite
|
Sign up to set email alerts
|

Residue and intake risk assessment of prothioconazole and its metabolite prothioconazole-desthio in wheat field

Abstract: In the environment, plants and animals in vivo, pesticides can be degraded or metabolized to form transformation products (TPs) or metabolites, which are even more toxic than parent pesticides. Hence, it was necessary to evaluate residue and risk of pesticides and their TPs (or metabolites). Here, a rapid, simple, and reliable method using QuEChERS and LC-MS/MS had been developed for simultaneous analysis of prothioconazole and its toxic metabolite, prothioconazole-desthio, in soil, wheat plant, straw, and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The following formulas are adopted to evaluate the long‐term dietary intake risk of pyraclostrobin or picoxystrobin: 17,18 NEDI=()STMRi×Fi/bw RQc=NEDI/ADI×100% …”
Section: Methodsmentioning
confidence: 99%
“…The following formulas are adopted to evaluate the long‐term dietary intake risk of pyraclostrobin or picoxystrobin: 17,18 NEDI=()STMRi×Fi/bw RQc=NEDI/ADI×100% …”
Section: Methodsmentioning
confidence: 99%
“…Also, there still lacks an effective method that can determine the severity of diseased wheat ear groups. In addition, all the previous studies, evaluating the effects of fungicide applications on the control wheat FHB [35]- [36], employ a manual assessment method by counting the number of wheat ears affected to determine the efficacy of fungicide application programs [37]. Such traditional disease severity assessment method is laborious and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the major prothioconazole metabolites 26 with higher activity 25 and greater toxicity 27 to rats. 26,[28][29][30] Although lots of previous studies showed that chiral triazole fungicides could be well separated by HPLC, 31,32 there are limited studies on the chiral resolution of prothioconazole or prothioconazole-desthio at normal and reverse phase conditions. 26,[28][29][30] Although lots of previous studies showed that chiral triazole fungicides could be well separated by HPLC, 31,32 there are limited studies on the chiral resolution of prothioconazole or prothioconazole-desthio at normal and reverse phase conditions.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Prothioconazole-desthio, (2RS)-2-(1-chlorocyclopropyl)-1-(2-chlorophenyl)-3-(1H-1,2,4-triazol-1-yl) propan-2-ol, is also a triazole compound in the enforced animal commodity residue definition (see Figure 1A). It is one of the major prothioconazole metabolites 26 with higher activity 25 and greater toxicity 27 to rats. Determination of prothioconazole and prothioconazole-desthio using HPLC and ultra performance liquid chromatographytandem mass spectrometry (UPLC-MS/MS) has been reported in animal food, soil, and wheat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation